4-Methylcoumarins with cytotoxic activity against T24 and RT4 human bladder cancer cell lines. Issue 5 (13th May 2015) - Vianna, D. R.; Ruschel, L.; Dietrich, F.; Figueiró, F.; Morrone, F. B.; Canto, R. F. S.; Corvello, F.; Velho, A.; Crestani, A.; Teixeira, H.; von Poser, G. L.; Battastini, A. M. O.; et al.
<x xml:space="preserve">Abstract</x> 4-Methylcoumarins were synthesized by microwave-assisted synthesis via Pechmann condensation and their cytotoxic activity against human bladder cancer cell lines was investigated.